PENGARUH KARAKTERISTIK WIRAUSAHA, PENGALAMAN DAN MOTIVASI TERHADAP KEBERHASILAN USAHA UMKM ( Studi di Desa Timbulharjo) - Intan Maharani Hartanti Candra (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This study aims to examine the variables of entrepreneurial characteristics, experience and motivation on business success in MSMEs in Desa Timbulharjo. The research design used is quantitative research. Sampling was done by simple random sampling method and carried out by distributing questionnaires. The sample involved as many as 87 SMEs in Desa Timbulharjo. Data analysis used in this study include; (1) text data instrument, (2) classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, (3) hypothesis testing. The results showed that there was no positive and significant effect on the entrepreneurial characteristics variable on business success. Meanwhile, the experience and motivation variables have a positive and significant influence on business success.